Pengaruh Motivasi, Pemahaman, Sikap, Norma Subjektif, Kontrol Perilaku Persepsian Terhadap Niat Mahasiswa Akuntansi Untuk Mengikuti Sertifikasi Akuntan Profesional Chartered Accountant (CA) - Adiva Salsabila; Rieska Maharani; Ma'ruf Sya'ban (SUSTAINABLE JURNAL AKUNTANSI, 2022)
The Influence of Motivation, Understanding, Attitudes, Subjective Norms, and Perceived Behavioral Control on the Intention of Accounting Students to Take Chartered Accountant (CA) Professional Accountant Certification. A person is considered a professional as evidenced by a professional certification. The purpose of this study was to determine the influence of motivation, understanding, attitudes, subjective norms and perceived behavioral control on the intention of accounting students to take the Chartered Accountant (CA) professional accountant certification. This study uses quantitative methods with an explanatory research approach. The population used were undergraduate accounting students at University of Muhammadiyah Surabaya, STIESIA Surabaya, Airlangga University Surabaya, and the National Development University "Veteran" East Java Surabaya. The sampling technique used is the Purposive Sampling technique with a total of 98 students. Data was collected using a questionnaire which was measured using a Likert scale. Test The research instrument used is validity test and reliability test, classical assumption test used is normality test, multi collinearity test, and heteroscedasticity test. The hypothesis test used is multiple linear analysis test and t test. The results in this study indicate that motivation and subjective norms have a positive and significant effect on the intentions of accounting students, while attitudes and perceived behavioral control have a positive and insignificant effect on the intentions of accounting students, and understanding has a negative and insignificant effect on the intentions of accounting students to take accountant certification. professional Chartered Accountant (CA).